PERAN DINAS PARIWISATA PROVINSI BALI DALAM IMPLEMENTASI CHSE PADA HOTEL DAN RESTORAN DI BALI - Kresnanda Yuliono; I Nyoman Sudiarta; IGPB. Sasrawan Mananda (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
Bali is a province whose economic sector is dominated by the tourism industry and is one of the victims of the impact of restrictions on the movement of world tourists caused by Covid-19. PHRI published since the beginning of the pandemic until April 2020 there were 281 hotels and 19 restaurants in Bali that had stopped operating. Kemenparekraf helps the Bali Government Tourism in taking a role for the recovery of the tourism industry and continue to operate in the pandemic situations. This study aims to explain the role of the Bali Government Tourism during the Covid-19 pandemic in implementing CHSE in hotel and restaurant businesses in Bali. This study uses a qualitative method with purposive techniques in determining informants, namely the Bali Provincial Tourism Office, PHRI Bali, hotel and restaurant business actors in the Sanur, Ubud and Nusa Dua areas. Data was collected by means of structured and open interviews. The data analysis technique used is descriptive qualitative. The results of the study explain that the role of the Bali Provincial Tourism Office as a facilitator, regulator and catalyst is implemented with programs that is carried out as well as the implementation of CHSE to suppress the spread and education of Covid-19 prevention in hotel and restaurant businesses and gain the trust of potential tourists to come to Bali so that the wheels of the economy Bali goes on. All of these activities involve various parties such as associations, academics, government institutions, national media, business actors, Balinese people to tourists who are stay in and want to go to Bali.